Small letters Using the literary platform to portray health crises (مجلة إحالات, 2026)
Literature acquires its value when it touches the various human issues facing the individual, especially when it mixes the literary experience with the creative touch, thus imparting an artistic formula of an aesthetic nature. An obsession with the fear of losing his life due to an epidemic or a life threateningpandemic that swept the world, so the writers were the first to interact with these painful events that forced them into long isolation, as their pens exploded expressing their feelings and illustrating the experiences theylived through, so a new genre emerged in the literary arena locally and globally. It was called pandemic literature, and this literary genre invaded the world of poetry, stories, and novels.From this standpoint, this research paper came to answer the following questions: How did writersface these crises? To what extent did they interact with it? What is the impact of this on the Arab andinternational audience? Will a new literature be established for this type of literature?